Impacts of the Crisis: Anticipating the Future - Marina Boykova; Diana Krupnikova (Foresight and STI Governance, 2009)
This paper is based on the materials of the online forum, organized by John Renesh, futurist, member of “Shaping Tomorrow’s Foresight Network”. The authors use some materials of the discussion held in frameworks of this forum, and discuss questions connected with preconditions of today’s financial crisis, its effects and plan of ways out.